The Efficacy of Short-term Gated Audiovisual Speech Training for Improving Auditory Sentence Identification in Noise in Elderly Hearing Aid Users - Moradi, Shahram; Wahlin, Anna; Hällgren, Mathias; Rönnberg, Jerker; Lidestam, Björn (Frontiers in Psychology, 2017)
This study aimed to examine the efficacy and maintenance of short-term (one-session) gated audiovisual speech training for improving auditory sentence identification in noise in experienced elderly hearing-aid users. Twenty-five hearing aid users (16 men, 9 women), with an average age of 70.8 years, were randomly divided into an experimental (audiovisual training, n = 14) and a control (auditory training, n = 11) group. Participants underwent gated speech identification tasks comprising Swedish consonants and words presented at 65 dB sound pressure level with a 0 dB signal-to-noise ratio (steady-state broadband noise), in audiovisual or auditory-only training conditions. The Hearing-in-Noise Test was employed to measure participants’ auditory sentence identification in noise before the training (pre-test), promptly after training (post-test), and one month after training (one-month follow-up). The results showed that audiovisual training improved auditory sentence identification in noise promptly after the training (post-test vs. pre-test scores); furthermore, this improvement was maintained one month after the training (one-month follow-up vs. pre-test scores). Such improvement was not observed in the control group, neither promptly after the training nor at the one-month follow-up. However, no significant between-groups difference nor an interaction between groups and session was observed. Conclusion: Audiovisual training can be used by hearing aid users may beas considered inan effective and clinically relevant aural rehabilitation of hearing aid users program to promoteimprove their listening capabilities capabilities in noisy conditions. However, the lack of a significant between-groups effect (audiovisual vs. auditory) or an interaction between group and session calls for further research.